Principles of estimation of synthetic working fluids condition in aviation hydraulic systems - Мухояров, И. Н. (Proceedings of National Aviation University (archive), 1999)
Considered are the possibilities of predicting hydraulic systems reliability by the analysis results of the used fluids and by obligatory use of combined indexes, characterizing fluid condition. Using synthetical working fluids НГЖ-4 and НГЖ-4у as example considered are controlled parameters - wearing of antioxidant additive and viscosity change - can characterize aging of used synthetic fluids and determine actual operation life of fluids in hydraulic systems